Brand Trust Can Moderates The Influence of Rating Reviews on Purchasing Decisions: Penelitian - Muhamad Risal Tawil; Gilang Pranajasakti; Fahad Ramadhan; Dimas Realino; Nova Ch. Mamuaya (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Amidst the escalation of digital economic competition in 2026, this study aims to investigate the interaction mechanism between online rating reviews and consumer purchasing decisions by placing brand trust as a moderating variable. Integrating Signaling Theory and Trust-Transfer Theory , this quantitative study uses a causal-explanatory approach to 450 active e-commerce user respondents who were analyzed through the Moderated Regression Analysis (MRA) technique using E-Views 12 software . The empirical test results prove that although rating reviews are a significant external signal in reducing information asymmetry, their effectiveness in triggering transactions is highly dependent on the level of brand trust held by consumers; where brand trust functions as a psychological filter that validates the credibility of the review. These findings reveal a moderation phenomenon whereby for brands with high trust equity, the influence of positive reviews is significantly amplified, while for brands with low trust, positive reviews are often met with cognitive skepticism that hinders purchase conversion.The practical implications of this study emphasize that marketing managers should prioritize building long-term brand loyalty and trust over simply manipulating short-term ratings to ensure sustainable market value in an era of digital sentiment volatility.